2021
DOI: 10.1161/circheartfailure.120.007433
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicated Donors and Heart Transplant Outcomes: Long-Term Safety

Abstract: Background: The opioid crisis has led to an increase in available donor hearts, although questions remain about the long-term outcomes associated with the use of these organs. Prior studies have relied on historical information without examining the toxicology results at the time of organ offer. The objectives of this study were to examine the long-term survival of heart transplants in the recent era, stratified by results of toxicological testing at the time of organ offer as well as comparing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Previous work has demonstrated that the use of donors with history of drug use or toxicology positive for ≥1 drugs is not associated with long-term differences in mortality. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work has demonstrated that the use of donors with history of drug use or toxicology positive for ≥1 drugs is not associated with long-term differences in mortality. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Previous work has conclusively shown that donor drug history does not impact the posttransplant survival, though that is among donors who are selected for transplant (which leads to significant bias). 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients who have received other donor organs, for example, liver and kidney, have higher rates of death and graft failures [ 49 ]. A long-term study completed by Baran et al saw no significant difference in survival between recipients who received a donor heart with a history of drug abuse compared to those who do not [ 50 ]. A more lenient view of OODDs hearts will help further to expand the donor pool.…”
Section: Reviewmentioning
confidence: 99%